Changes in Volatile Compound Composition of Kensington Pride Mango Pulp During Fruit Ripening - Herianus J.D Lalel (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Volatile compounds of ‘Kesington Pride’ mango produced from the pulp during fruit ripening were studied using headspace solid-phase microextraction (SPME) as a sampling method and gas chromatography with a flame ionisation detector (GC-FID) and gas chromatography mass spectrophotometry (GC-MS) for analysis. Ethylene production and respiration reached a peak on the second and third day of ripening, respectively. Seventy-eight volatile compounds were identified from the pulp of ‘Kesington Pride’ mango; however, only 73 volatile compounds were present in notable amount. The most abundant group of volatile compounds was monoterpenes, accounting for abaout 44% of the total identified compounds, followed by sesquiterpenes (19%), aldehydes (11%),esters (10%) aromatics (8%), alcohol (2%), ketones (2%), alkanes (1%) and norisoprenoid (1%). -Terpinolene was the major compound during ripening. Except for -pinene, 3,7-dimethl-1,3,7-octatriene, 4-methl-1 (1-methylethylidene)-cyclohexene, p-mentha-1,5,8-triene, aloocimene, the concentration of all other monoterpenes increased for the first six or eight days and decreased afterwards. All sesquiteroenes, p-cymene, p-cymen-9-ol,2-ethyl-1,4-dimethl benzene also increased during ripening and peaked on day four, six or eight of ripening. Ketones, aldehydes alkane and cis-3-hexenol, on the other hand, decreased during ripening. Ethanol, esters and norisoprenoid increased quite sharply at the end of ripening period. Key words : Manggo, aromatic, ripening.